Effects of charge compensator Li+ co-doping on the structure and luminescence properties of Cd2V2O7:Eu3+ red phosphors. Issue 8 (1st June 2018) - Zhang, Wentao; Yan, Guilin; Dai, Siyi; Zhang, Peicong; Zhao, Qingdong; Qiu, Kehui; Deng, Miao
Abstract: A series of Cd2 V2 O7 :Eu 3+, Li + red phosphors was prepared by a solid-state reaction method. A pure Cd2 V2 O7 phase with monoclinic structure was obtained by heating to a temperature range of 600–850 °C. The effects of Eu 3+ doping and Li + co-doping concentrations on the luminescence properties of Cd2 V2 O7 :Eu 3+, Li + samples were investigated. Under excitation at 375 nm, the as-prepared Cd2 V2 O7 :Eu 3+ phosphors exhibit a red emission peak at 618 nm due to the 5 D0 → 7 F2 electronic transition of Eu 3+ . The luminescence properties of Cd2 V2 O7 :Eu 3+, Li + samples are improved significantly by the addition of Li + as charge compensator compared to the Cd2 V2 O7 :Eu 3+ phosphor. The results indicate that Cd2 V2 O7 :Eu 3+, Li + phosphor could be a promising red phosphor in near ultraviolet-excited white light-emitting diodes for warm white light.